Revision of the family Carabodidae (Acari: Oribatida) II: Redescription of Austrocarabodes ensifer (Sellnick, 1931), Aokiella florens Balogh & Mahunka, 1967 and Singabodes rarus Mahunka, 1998 - Fernández, Néstor Alfredo (2012)
Austrocarabodes ensifer (Sellnick, 1931) is redescribed and illustrated based on adult specimens using optical microscopy as well as scanning electron microscopy. Aokiella florens Balogh & Mahunka, 1967 and Singabodes rarus Mahunka, 1998 are redescribed and figured based on adult specimens using optical microscopy only. These three species are the type species of their respective genera, thus allowing us to redefine each. Although it is likely that Singabodes may be a synonym for Aokiella, further study is necessary to resolve the uncertainty.